Pengaruh Tingkat Retensi Pajak, Beban Pajak Tangguhan, Aset Pajak Tangguhan dan Return On Assets Terhadap Manajemen Laba Pada Perusahaan Manufaktur Sub-Sektor Makanan dan Minuman di Bursa Efek Indonesia Periode 2020 - 2022 - Putri Rais, Rany Gesta; Nur Afni Yunita; Yusra, Muhammad; Endah Rizki Ayunda (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
: This research aims to determine the effect of tax retention rate, deferred tax, deferred tax assets and Return On Assets on earnings management in food and beverage sub-sector manufacturing companies listed on the Indonesian stock exchange in 2020-2022. The sample used in this research was 24 companies using the purposive sampling method. The research results show that the variables deferred tax expense and Return On Assets have an effect on the earnings management variable. Meanwhile, the variable level of tax retention and deferred tax assets do not have a significant effect on the earnings management variable. Keywords : Tax Retention Rate, Deferred Tax, Deferred Tax Assets, Return On Assets, Earning Management